1995
DOI: 10.1002/jcp.1041630121
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress modulates endothelial cell morphology and F‐actin organization through the regulation of focal adhesion‐associated proteins

Abstract: Flow-related shear stress has been shown to modulate endothelial cell structure and function including F-actin microfilament organization. Focal adhesion-associated proteins such as vinculin, talin, and specific integrins may play a role in the modulation of these cytoskeletal and morphological changes. Double-label immunofluorescence studies indicated that, in static culture, alpha 5 beta 1 fibronectin receptors (alpha 5 beta 1 FNRs) and alpha v beta 3 vitronectin receptors (alpha v beta 3 VNRs) were found pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
150
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(155 citation statements)
references
References 60 publications
2
150
2
Order By: Relevance
“…Several studies have suggested that strain increases cell proliferation by increasing autocrine production of PDGF. 7,32 With avian tendon cells, however, synergistic action of both load and PDGF is required for enhancement of cellular proliferation. 33 Several cytokines have been shown to stimulate cell proliferation [34][35][36][37][38] and cell migration 35 of ACL and MCL cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that strain increases cell proliferation by increasing autocrine production of PDGF. 7,32 With avian tendon cells, however, synergistic action of both load and PDGF is required for enhancement of cellular proliferation. 33 Several cytokines have been shown to stimulate cell proliferation [34][35][36][37][38] and cell migration 35 of ACL and MCL cells.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Application of mechanical load also influences cell proliferation, differentiation, and gene expression in a wide variety of cells; [3][4][5][6][7][8][9][10][11][12][13] however, the molecular mechanisms have not been well defined. Mechanical deformation of the cell or matrix is sensed by specific interactions between extracellular matrix molecules and membrane proteins including the family of transmembrane proteins known as integrins.…”
Section: Introductionmentioning
confidence: 99%
“…34 -42 For instance, altered fluid shear stress influences the activities of mitogen-activated protein kinases 43,44 and G proteins, 45 the production rate of prostacyclin, 46 the activities of growth factors, 26,33,35,47,48 and the morphology 49,50 and cytoskeletal structure 51 of endothelial cells. These changes have been implicated in the mediation of mechanical stress-related vascular atherogenesis.…”
Section: Role Of Signaling Molecules and Growth Factors In Mechanicalmentioning
confidence: 99%
“…While it is clear that the transport of oosperm involves smooth muscle contraction [1,2], the detailed mechanism still remains elusive [1][2][3][4][5][6][7], due in part to the complexity of cellsubstrate interactions via receptor-ligand binding as well as various physical forces inside and outside of the cytoskeleton [8][9][10][11][12]. Cells are known to respond to mechanical forces exerted through surrounding fluid, adhering beads or substrates [9,[12][13][14], and they could detach, slip or roll on a substrate in response to these forces [15][16][17][18][19][20][21][22]. For example, cells on a cyclically stretched substrate tend to reorient themselves away from the stretching direction [23][24][25][26][27], and cells migrate along a substrate with rigidity gradient (durotaxis) [18].…”
Section: Introductionmentioning
confidence: 99%